Will your proposals hit the mark? (2008)
Notes that judgement and decisions are strongly affected by the amount of information received and the way in which it is framed. Suggests therefore that negotiators can use a number of influence strategies to reach their goals. Provides five strategies that will help one to present offers with maximum effectiveness.
Keywords: STRATEGIC PLANNING